Kultur akar rambut Cinchona ledgeriana dan C. succirubra dalam kultur in vitro Hairy root culture of Cinchona ledgeriana and C. succirubra by in vitro culture - Nurita TORUAN-MATHIUS; . REFLINI; . NURHAIMI-HARIS; . JOKO-SANTOSO; A PRIANGANI-ROSWIEM (INDONESIAN OIL PALM RESEARCH INSTITUTE, 2004)
Summary Problems encountered in hairy root culture of C. ledgeriana and C. succirubra are low percentage of transformation of explants by Agrobacterium rhizogenes and slow growth of hairy root. The objective of this research was to evaluate the potential of several A. rhizogenes strains for initiation hairy roots of C. succirubra and C. ledgeriana, and to obtain the best medium for hairy root culture of Cinchona spesies. Axenic shoot and leaves explants of eight-month-old of C. ledgeriana and C. succirubra seedlings were inoculated with A. rhizogenes strain ATCC-15834, ATCC-8196, R-20001, 07-20001, A4, R-MAFFA, TISTR509, TISTR510 and LBA9457. Inoculated explants were cultured in solid MS medium with the addition of 100 mg/L amphicylin. Subculture of the hairy root was performed by transferred of root pieces into fresh liquid basal medium MS, B5, White and Heller. Hairy roots from the best of basal medium were subcultured on the same medium with the addition of 50 and 100 mg/L L-tryptophane, three or five times concentration of MS vitamins. The integration of T-DNA of A. rhizogenes in hairy root was confirmed with specific primer for TL and TR-DNA of plasmid by Polymerase Chain Reaction analysis. The results showed that only A. rhizogenes strain LBA 9457 were effective for transformation of explants from both Cinchona species. The fastest hairy roots growth were found in MS medium, while growth in others medium was poor. Hairy roots of C. ledgeriana has vigor and growth better than hairy roots of C. succirubra. MS with the addition of 50 mg/L L-tryptophane and three times the concen-trations of vitamin is the best medium for hairy root growth and vigor. Hairy roots of C. succirubra and C. ledgeriana used in this studies were confirmed that hairy roots contained TL and TR-DNA region of Ri plasmid with molecular weight 780 and 1600 bp. The results showed that strain of A. rhizogenes, plant species, source of explant and composition of medium affect the initiation, growth, development and vigor of hairy roots.Ringkasan Masalah dalam kultur akar rambut C. ledgeriana dan C. succirubra adalah rendahnya tingkat keberhasilan transformasi eksplan dengan Agrobacterium rhizogenesdan pertumbuhannya yang lambat. Penelitian ini bertujuan untuk mengevaluasi potensi dari beberapa galur A. Rhizogenes untuk inisiasi, mendapatkan komposisi medium terbaik untuk pertumbuhan akar rambut C. ledgeriana dan C. succirubra, serta konfirmasi terintegrasinya TR dan TL-DNA Ri plasmid ke dalam jaringan eksplan. Eksplan batang dan daun berasal dari kecambah aksenik C. ledgeriana dan C. succirubra berumur delapan bulan diinokulasi dengan A. rhizogenes galur 15834, 8196, R-20001, 07-20001, A4, R.MAFFA,TISTR 509, TISTR 510 dan LBA 9457. Eksplan yang sudah diinokulasi dikulturkan dalam medium MS padat. Subkultur dilakukan dengan cara mentransfer potongan ujung akar rambut ke dalam medium cair MS, B5, White dan Heller. Akar rambut dari medium kultur yang terbaik kemudian disubkultur ke dalam medium yang sama dengan penambahan 50 dan 100 mg/L L-triptofan dengan konsentrasi vitamin sebanyak tiga kali dan lima kali dari konsentrasi normal MS. Integrasi T-DNA dalam akar rambut dikonfirmasi meng-gunakan Polymerase Chain Reaction dengan primer spesifik untuk TL dan TR-DNA plasmid. Hasil yang diperoleh menunjukkan bahwa hanya A.rhizogenes galur LB9457 yang efektif menginfeksi eksplan baik batang maupun daun dari kedua spesies kina. Induksi, pertumbuhan dan vigor akar rambut yang terbaik diperoleh dari medium MS dengan penambahan 50 mg/L L-triptofan dan tiga kali konsentrasi vitamin. Hasil konfirmasi akar rambut baik dari batang maupun daun menggunakan PCR, menunjukkan bahwa TL dan TR-DNA dari Ri plasmid A. rhizogenes mampu menghasilkan pita-pita DNA dengan BM780 dan 1600 pb. Hasil yang diperoleh menunjukkan bahwa galur A. rhizogenes, spesies tanaman, sumber eksplan dan komposisi medium berpengaruh terhadap inisiasi, pertumbuhan, perkembangan dan vigor akar rambut.